Большая книга для детей: [рассказы, сказки и стихи] / Владимир Степанов - Степанов Владимир Александрович (Оникс, 2010)
Экземпляры: М/а ДБ (20111220) / Инвентарный номер: 97742 / Цена: 205.60 / Авт.знак: С 79 / ГРНТИ: 17.82 / ББК: 84(2=411.2)6